Systematic Literature Review on Opportunities for Digital Innovation in the Healthcare Sector - Osembe, Lufungula; Adebesin, Funmi; Smuts, Hanlie (Journal of Health Informatics in Africa, 2024)
Background and Purpose: The concept of digital innovation has garnered significant attention recently and has the potential to revolutionise industries. With the recent advancements in healthcare and the emergence of new digital technologies, this manuscript reports the results of a systematic literature review (SLR) aimed at identifying the opportunities that digital innovation can afford the healthcare sector. These opportunities could guide policymakers and healthcare practitioners in making informed decisions regarding the implementation of digital innovation in healthcare. Methods: This study conducted a systematic literature review (SLR) that involved defining the purpose of the literature review, establishing inclusion and exclusion criteria, identifying data sources and search strategies, screening and determining eligibility, and making inclusion/exclusion decisions. This study also included quality assessment criteria to evaluate the selected publications. 1478 research papers were analysed using descriptive statistics and thematic analysis to identify themes from the papers included in the SLR. Results: The findings presented nine themes related to opportunities for digital innovation in healthcare. The following themes were discussed: precision/personalised medicine/healthcare, interoperability, privacy and security, improved decision-making process, real-time/remote monitoring, enabling new processes/services/products, training/education, knowledge acquisition/sharing, and other themes that could not be categorised. These themes include cost, effectiveness, and time management. Conclusions: This study utilised thematic analysis to examine the themes that emerged from the findings. These themes centred around the opportunities for digital innovation in healthcare. Awareness about each opportunity for digital innovation in healthcare is discussed. This study discussed the limitations of this SLR and future research opportunities for policymakers and healthcare practitioners wanting to implement digital innovation in healthcare.